1996
DOI: 10.1161/01.cir.94.9.2248
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Environmental Tobacco Smoke on LDL Accumulation in the Artery Wall

Abstract: Exposure to ETS acutely increased LDL accumulation in perfused arteries. Repeated exposure to ETS may represent important early events in atherogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
4

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 21 publications
0
26
0
4
Order By: Relevance
“…This effect appears to be related to modification of LDL by the products of environmental tobacco smoke, a process that may occur in blood. 30 We saw a tendency for MM-LDL to accumulate in the artery wall to a greater extent than did OX-LDL. This could result from a number of possible mechanisms, including induction of substances that increase endothelial layer permeability, such as cytokines (eg, tumor necrosis factor-␣).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…This effect appears to be related to modification of LDL by the products of environmental tobacco smoke, a process that may occur in blood. 30 We saw a tendency for MM-LDL to accumulate in the artery wall to a greater extent than did OX-LDL. This could result from a number of possible mechanisms, including induction of substances that increase endothelial layer permeability, such as cytokines (eg, tumor necrosis factor-␣).…”
Section: Discussionmentioning
confidence: 77%
“…6,30 Rats were anesthetized by intraperitoneal injection of sodium pentobarbital (35 mg/kg). After the rat was anesthetized, a midline incision was made in the neck, and both carotid arteries were dissected free from connective tissue.…”
Section: Experimental Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance, 2 to 4 hours of exposure of rats to environmental tobacco smoke has recently been shown to increase LDL accumulation in perfused arteries. 26 An increasing number of reports has documented the harmful effects of environmental tobacco smoke. [27][28][29] We found that a short period of passive smoking changed LDL metabolism, favoring the progression of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Some papers from the 1990s reported that exposure to environmental tobacco smoke increases the risk of atherosclerosis (16).…”
mentioning
confidence: 99%